YODA++: A proposal for a semi-automatic space mission control - Casolino, M.; De Pascale, M.P.; Nagni, M.; Picozza, P. (Advances in space research, 2006)
YODA++ is a proposal for a semi-automated data handling and analysis system for the PAMELA space experiment. The core of the routines have been developed to process a stream of raw data downlinked from the Resurs DK1 satellite (housing PAMELA) to the ground station in Moscow. Raw data consist of scientific data and are complemented by housekeeping information. Housekeeping information will be analyzed within a short time from download (1 h) in order to monitor the status of the experiment and to foreseen the mission acquisition planning. A prototype for the data visualization will run on an APACHE TOMCAT web application server, providing an off-line analysis tool using a browser and part of code for the system maintenance. Data retrieving development is in production phase, while a GUI interface for human friendly monitoring is on preliminary phase as well as a JavaServerPages/JavaServerFaces (JSP/JSF) web application facility. On a longer timescale (1–3 h from download) scientific data are analyzed. The data storage core will be a mix of CERNs ROOT files structure and MySQL as a relational database. YODA++ is currently being used in the integration and testing on ground of PAMELA data.